LITERETURE REVIEW FACTORS AFFECTING EMPLOYEE PERFORMANCE : COMPETENCE, COMPENSATION AND LEADERSHIP - Az Zahra Tania Arifani; Azzalia Yuniar Susanti (Dinasti Publisher, 2020)
The rapid development of the times accompanied by increasingly sophisticated technology has an impact on various company activities, especially on managerial aspects. Even though companies and organizations have modern technology, companies are still tied to human labor. Human resources are an important factor in an organization so that humans are a strategic factor in organizational management. Human resources are very important to be given direction and guidance from human resource management in order to produce optimal performance. Employee performance is an individual matter depending on the level of different qualifications of each individual which reflects the quantity and quality of something that is produced or done by the worker. This research was conducted by looking at the three factors that are considered to have an effect on employee performance, namely competency, compensation, and leadership style factors through various relevant research methods and can explain in detail the relationship between performance factors